Fish resource exploitation in the southern Atlantic coast of the Iberian Peninsula: A view from the traceological analysis of flaked stone tools (sixth-fourth mill. cal BCE) - Clemente-Conte, Ignacio (2020)
In this paper, we provide new data on fish resource exploitation during the Mesolithic and Neolithic period on the Atlantic coast of the Iberian Peninsula. Evidence from four different sites is presented: Vale Marim I (end of the seventh/beginning of the sixth millennium cal BCE) and Vale Pincel I (2nd and 3rd quarters of the sixth millennium cal BCE), both located on the southwestern Portuguese coast, and La Esparragosa and SET Parralejos (fourth-third millennia cal BCE), both located on the southern Spanish coast. The analysis of the lithic assemblages by means of use-wear analysis provided evidence of fish-processing activities. The analysis of the archaeological tools has been based on a renewed experimental framework for fish-related use-wear traces. Despite data being still scarce and fragmentary, this study points out the necessity of a more integrating approach, including traceological analysis in the framework of a broader research on prehistoric fishing.